Reconstructing Social Assistance Distribution: Tafsir Maqashidi on Quranic Verses of Distributive Justice - Afifi, Mansur; Fachrurrozi, Fachrurrozi; Nikmatullah, Nikmatullah; Abdul Salam, Sobihatun Nur (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2025)
This article seeks to reevaluate the concept and distribution of social assistance as a means to achieve distributive justice. Utilising the Tafsīr Maqāṣidī approach — an interpretation that reflects God's intentions—this study reconstructs the principles and methods of distributing social assistance to effectively realise distributive justice. The primary focus is on Qur'an Surah Al-Hashr [59]:7, which delineates the guidelines for distributing wealth collected by the government, referred to as al-Fai’. The findings indicate that the distribution of al-Fai’ in the form of social assistance is designed to prevent the concentration of wealth among affluent groups, ensuring that resources are shared with the poor and marginalised (ḍu‘afā’), thereby mitigating societal inequality. From the perspective of Maqāṣid al-Sharī‘ah, the provision of social assistance aims to safeguard religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), and the state (ḥifẓ al-Dawlah). Furthermore, social assistance embodies principles of justice (al-‘adālah), humanity (al-Insāniyyah), equality (al-Musāwāh), freedom (al-ḥurriyah), and responsibility (al-Mas’ūliyyah). Consequently, it is deemed unacceptable for the distribution of social assistance to be exploited for personal gain or to secure public office. Additionally, applying the Tafsīr Maqāṣidī approach in this context demonstrates how the maqāṣidī -based normative framework can evaluate the ethical soundness of government-initiated programs like social assistance. This research contributes to developing public policy by using the tafsir approach, in this study using Tafsīr Maqāṣidī.